Microbial Cross-Talk: Dissecting the Core Microbiota Associated With Flue-Cured Tobacco (Nicotiana tabacum) Plants Under Healthy and Diseased State - Ahmed, Waqar; Dai, Zhenlin; Liu, Qi; Munir, Shahzad; Yang, Jun; Karunarathna, Samantha C.; Li, Shichen; Zhang, Jinhao; Ji, Guanghai; Zhao, Zhengxiong (Frontiers in Microbiology, 2022)
Bacterial wilt caused by Ralstonia solanacearum is a devastating disease of flue-cured tobacco production poses significant yield losses. In this study, we evaluated the rhizosphere microbiome of healthy and bacterial wilt-infected (diseased) flue-cured tobacco plants through amplification of V3-V4 and ITS1-5f variable regions of 16S and ITS rRNA. The study was based on location (Qujing, Shilin, and Wenshan), plant components (rhizosphere soil and roots), and sample types (healthy and diseased) to assess the diversity of bacterial and fungal communities. Bacterial and fungal communities present in roots primarily emanated from rhizosphere soil. Healthy flue-cured tobacco plants exhibit high microbial diversity compared to diseased plants. Among three variables, plant components significantly influence the diversity of microbial communities, while rhizosphere soil harbors higher microbial diversity than roots. Bacterial phyla Cyanobacteria and Proteobacteria were found in high relative abundance in roots and rhizosphere soil samples, respectively. As far as fungi is concerned, a high relative abundance of Ascomycota and Basidiomycota was found in both rhizosphere soil and root. Bacterial genera such as Bacillus, Bradyrhizobium, Ensifer, Neorhizobium, and Lysobacter related to plant growth promotion and disease suppressing abilities were dominant than fungal genera of Gibberella and Purpureocillium. Analysis of relative abundance at species revealed that most fungal species are pathogenic to flue-cured tobacco could be the main reason for tobacco bacterial wilt disease. We conclude that R. solanacearum significantly influences the microbial diversity of flue-cured tobacco plants and negatively affects the bacterial community composition. Altogether, our study demonstrates the complexity of bacterial and fungal communities that possibly interact with each other (microbe-microbe) and host (host-microbe). This cross-talk could be helpful for healthy flue-cured tobacco plant growth and to induced resistance against bacterial wilt disease.